Understanding the determinants of e-wallet continuance usage intention in Malaysia - Abdul-Halim, Nurul-Ain (2022)
The present research aims to investigate the determinants of e-wallet continuance usage intention in Malaysia using extending Technology Continuance Theory (TCT) via examining four variables, namely price benefit, trust, habit, and operational constraints. This paper adopts a quantitative approach to collect data with non-probability sampling using the purposive sampling technique. An online survey was conducted and a total of 379 respondents submitted their answers. The obtained results have shown that continue use of e-wallet is not affected by perceived usefulness (PU) and trust. However, there is a significant influence associated with perceived ease of use (PEU), PU, and satisfaction toward user’s attitude that, in turn, substantially impacts the users’ intention to continue to use e-wallet. This is one of the prior studies exploring Malaysian's intention to continue using e-wallet, using the TCT model as the research framework, and through examining four variables adopted from the literature, including price benefit, habit, trust, and operational constraints. The practical implications for the service providers and policymakers from the present findings can be used to develop strategies to gain a sustainable, competitive advantage, and promote continuous intention of e-wallet usage.